A novel species of Apiospora from Ulmus pumila in China - Yin, Xiaoye; Jiang, Ning (Phytotaxa, 2024)
Apiospora (Apiosporaceae, Amphisphaeriales) is a common genus distributed on various substrates globally. Members in this genus are usually known as endophytes and saprobes, sometimes phytopathogens. Two new strains of Apiospora were isolated from healthy leaves of Ulmus pumila in Beijing, China. Identifications were conducted based on morphological features and phylogeny of combined sequences of ITS, tef1 and tub2 loci. As a result, Apiospora ulmicola sp. nov. is proposed herein, which is different from its phylogenetically close species, Ap. intestini by much smaller conidia.